Manejo de cortinas para mejorar el bienestar animal y parámetros productivos en pollos cobb 500 - Cedeño Mendoza, Karen Alexandra (2017)
Ammonia was measured the first 14 days of life through an ammonia meter (ppm). We assessed the control group and treatment: T0 was handled in traditional mode blinds and T1 was handled in curtains every two hours from 7 am to 5 pm from day one to fourteen for air exchange. A total of 200 Cobb 500 chicks were distributed in two groups. The variables studied were: starting weight, final weight, weight gain, daily weight gain, ammonia levels, feed intake, feed conversion, european efficiency index, mortality and cost benefit. The best weight at week 2 was obtained at T0 with 463,9g and final weight of 2580,6g at T1, the best weight gain of week 2 and 6 was with T0 at 317,45g and 469,46g, the best daily weight gain was with T1 at 60,34g, the highest food intake of week 2 was with T1 at 471,35g and in week 6 with T0 at 1032,92g, the food conversion was more efficient at T1 with 1,71, in the adjusted food conversion, the T1was the best, failing to gain 0,03 ctvs, the T1 obtained a 349,74 european efficiency index and the the lowest ammonia level was obtained in the same T1 at 2,64 ppm. The mortality was equal in both groups at 1%, the cost benefit occurred in T1 with a profitability of 1.13 usd. It is concluded that the T1 obtained better answers in the majority of the variables.